Diversity of diatoms in the lower Tien and Hau rivers - Hanh, Vo; Kha, Le Kinh (Academia Journal of Biology, 2012)
Analyzing of 54 samples collected in October 2009 and March - April 2010, we found 119 taxa plankton diatoms, belonging to 44 genera, 20 families, 2 orders of Bacillariophyta, of those centrales diatoms are dominant. There are two more diverse families Coscinodiscaceae and Naviculaceae. In the lower Tien and Hau rivers the numerous genera (with more species/subspecies) are: Coscinodiscus (14 species), Chaetoceros (8), Rhizosolenia (6), Synedra (6), Pleurosigma (6), Biddulphia (5), Gyrosigma (5) and Navicula (5). Sorensen index is rather high (0.63 - 0.76), that indicated there is no significant difference in structure of plancton diatoms observed within the lower Tien and Hau rivers. Comparing the diversity of diatoms recorded within lower Tien and Hau rivers and the lower Ca river (Nghe An province) show that their total species has no so big difference, i.e. 119 vs 105, but there is a difference in the structure of species. In the lower Ca river the genera Coscinodiscus, Melosia, Navicula, Cymbella, Surirella, Chaetoceros and Gyrosigma are dominant. Using the method of canonical correspondence analysis (CCA) for considering the role of ecological factors on diatoms distribution shows that: in rainy season, the more important factors are transparence, water temperature, salinity (S‰) and DO (Ham Luong 1), while in dry season (at the same station) pH is more important (Ham Luong 2). In both seasons, the value of PO43-and NH4+ are important but not clearly demonstrated.